$\displaystyle 3x-2y=10$
$\displaystyle 5x+3y=15$
From the second equation you know that :
$\displaystyle 5x = 15 - 3y$
Thus $\displaystyle 15x = 45 - 9y$
And so, $\displaystyle 3x = 9 - 1.8y$.
Substituting back this result into the first equation gives :
$\displaystyle 9 - 1.8y - 2y = 10$
$\displaystyle 9 - 3.8y = 10$
$\displaystyle 3.8y = -1$
$\displaystyle y = \frac{-1}{3.8}$
Now substitute the value of $\displaystyle y$ found into any of the equations to retrieve $\displaystyle x$.
Can you do it for the second system now ?